IMPROVING PUBLIC AWARENESS OF EARTHQUAKE-RESISTANT HOUSE USING FACTOR ANALYSIS - Agus Dwi Hariyanto; Sugeng Triyadi; Andry Widyowijatnoko (DIMENSI (Journal of Architecture and Built Environment), 2020)
Public awareness of earthquake-resistant houses can increase the region's resilience to earthquake disasters. This study aims to conduct a comparison of two different groups of people on their opinion of earthquake-resistant housing variables and actions to increase the quality of their house. For supporting public awareness of earthquake-resistant houses, the purpose also determines the latent variables of earthquake-resistant houses and actions from the public for improving the quality of the residential building. This quantitative research begins by collecting the earthquake-resistant house attributes through journal reviews.  This study used a closed-ended questionnaire to collect data on public experiences of earthquake disasters. For data analysis, it used correlation analysis to determine the level of relationship between two variables and utilizes factor analysis to reduce the variable to a small number of factors. The two groups that have different experiences of earthquakes tend to have similar opinions about the characteristics of earthquake-resistant houses and the actions for improving the quality of residential buildings. The five factors of the earthquake-resistant housing are safe structural construction, fixed architectural elements, open accessibility, lightweight-ductile material, and simple floor plan. Then the three factors represent the actions for improving residential quality, namely, to improve material and structure, build an earthquake-resistant house, and make accessibility easy and safe.